Cellular mechanisms of impaired mineralocorticoid and glucocorticoid production by endocrine disruptor DDT - Yaglova, Nataliya V.; Obernikhin, Sergey S.; Yaglov, Valentin V.; Nazimova, Svetlana V.; Timokhina, Ekaterina P. (Experimental Biology and Biotechnology, 2021)
Developmental exposure to persistent endocrine disruptors is of a great concern. Affection of adrenal hormones production by low-dose exposure to dichlorodiphenyltrichloroethane (DDT) has been revealed recently. Objective of the research – investigation of ultrastructural mechanisms of impaired mineralocorticoid and glucocorticoid production after prenatal and postnatal exposure to endocrine disruptor DDT. Male Wistar rats exposed to low doses of DDT during prenatal and postnatal development were studied. Aldosterone and corticosterone levels in serum were measured by enzyme-linked immunosorbent assay, histological examination and electron microscopy of the adrenals were performed. Pubertal rats, developmentally exposed to low doses of DDT, demonstrated lowered aldosterone and elevated corticosterone serum levels. After puberty the rats showed tendency to normalization of hormones’ production. Morphological examination of the adrenals revealed less developed zona glomerulosa in pubertal period and its relative hyperplasia after puberty. Microcirculatory disorders and focal cell death were observed in outer zona fasciculata. Electron microscopy of glomerulosa cells found signs of suppressed secretory activity in pubertal period and no significant reduction of mitochondria size in adult rats. Total number of mitochondria in 1 µm2 of cytoplasm and percent of mitochondria with swollen matrix were diminished compared to the control. Cells of inner zona fasciculata demonstrated increased functional activity. Age-dependent changes in fine structure of fasciculata cells were similar to the control, but were more pronounced. In this way, cellular mechanism of impaired mineralocorticoid production in rats prenatally and postnatally exposed to low doses of endocrine disruptor DDT, are insufficient mitochondrion function and impaired reorganization of mitochondrial apparatus, which occurs during pubertal period. Mechanisms of elevated glucocorticoid secretion are attributed to enhanced function of mitochondria in fasciculata cells.
Keywords: mineralocorticoids; glucocorticoids; mitochondrion; endocrine disruptor; DDT